Metastatic lobular carcinoma of the breast masquerading as a primary rectal cancer - Matsuda, Ikuo (BioMed Central, 2012)
BACKGROUND: Colorectal metastasis of lobular carcinoma of the breast is a diagnostic challenge. It may macroscopically simulate primary colon cancer or inflammatory bowel disease. In some cases, the interval between the primary breast cancer and metastatic colorectal lesions is so long that the critical records for diagnosis including history might be lost or missed. CASE PRESENTATION: Reported herein is a case of metastatic lobular carcinoma of the breast masquerading as a primary rectal cancer developed in a 62-year-old Japanese woman. The case initially presented as a circumferential rectal lesion, and information on the patient’s history of breast cancer was not noted. As the result of endoscopic biopsy, diagnosis of poorly differentiated rectal adenocarcinoma was made. The lesion was surgically resected after chemo-radiotherapy. Histopathological examination of the resected specimen with hematoxylin and eosin (HE) stain revealed a single-file arrangement of the tumor cells, reminiscent of lobular carcinoma of the breast. Immunohistochemical analysis revealed an immunophenotype consistent with lobular carcinoma of the breast. Because further review of the patient’s history revealed an occurrence of ‘poorly differentiated adenocarcinoma of the breast’, which she had experienced 24 years earlier, the final diagnosis of the lesion was made as rectal metastasis from lobular breast carcinoma. CONCLUSIONS: Poorly differentiated adenocarcinoma of the colorectum is rarer than that of the stomach. Linitis plastica-type cancer of the colorectum is also rarer than that of the stomach. A lesson from the present case is that before we conclude a linitis plastica-type cancer of poorly differentiated type as a primary colorectal cancer, it is critical to exclude a possibility of metastatic colorectal cancer.